Mechanism of Ti99.2 titanium unconventional ion nitriding - Fraczek, Tadeusz; Michalski, Jerzy; Olejnik, Michal; Jasinski, Jaroslaw (International Conference on Plasma Surface Engineering, 2013)
Not available